Factors influencing dyspepsia-related consultation: differences between a rural and an urban population - Mahadeva, S.; Yadav, H.; Everett, S.M.; Goh, K.L. (Oxford, 2011)
Background  Dyspepsia is a common, chronic condition but medical consultation rates for symptoms remain variable. We aimed to examine two populations with varied health-care provision to determine predictive factors for dyspepsia-related consultation. Methods  A cross-sectional, population-based study in both an urban and a rural community within a single Asian country was conducted. Details on dyspepsia-related consultation rates over a fixed period and independent factors influencing them were identified. Key Results  A total of 4039/5370 (75.2%) adults from representative rural and urban areas in this country agreed to participate in the study. Although mean ages of respondents were similar (40.4 years), the demographics of both populations varied in terms of gender (62.7% female, rural vs 55.7% female, urban, P < 0.0001), marital status (75.4% rural vs 70.5% urban, P = 0.002), ethnicity, (79% Malay rural vs 45.3% Malays urban, P < 0.0001) and socio-economic status (professional occupation 7.1% rural vs 47.3% urban, P < 0.0001). Dyspepsia-related consultation rates were found to be higher among rural compared to urban adults (41.4%vs 28.7%, P < 0.0001). Over-the-counter medication consumption was higher among urban compared to rural dyspepsia sufferers (n = 157 vs n = 35, P < 0.0001). Following logistic regression, rural population (OR 3.14, 95% CI = 1.65-6.0), low quality of life (OR 1.90, 95% CI = 1.17-3.10), and self-medication (OR 0.40, 95% CI = 0.25-0.62) were found to independently predict dyspepsia-related consultation. Conclusions & Inferences  Dyspepsia-related consultation varied significantly between urban and rural communities. Factors within the rural population, self-medication practices, and a low quality of life independently influenced dyspepsia-related consultation.